Current IMT-2000 R&D status and views in Korea. - Wee, Kyu-Jin (IEEE Communications magazine)
In this article Korean development of IMT-2000 is considered. It includes the second-generation digital mobile communications, R&D and standardization activities related to IMT-2000, and the authors' perspectives on IMT-2000 in Korea. In Korea, there are many activities for development of IMT-2000 radio transmission technologies, and the results of these activities will be the submission of technologies to the ITU. However, the Korean telecommunications standardization body (TTA) will make every effort to make a common global standard for IMT-2000. Therefore, the TTA will make a domestic standard for IMT-2000 after the ITU finalizes the related Recommendations. It seems to the authors that difficulties in harmonization in the TTA are very similar to difficulties in harmonization worldwide. The only way of reaching the harmonization of IMT-2000 in Korea is that the key players should have the view from the end users' seat